Analysis of citations in the theses collection of the College of Arts and Sciences Reading Center, New Era University - Sibug, Michael D. (School of Library and Information Studies, University of the Philippines Diliman, 1999)
Citation analysis, a bibliometric study was used to analyze the characteristics of 533 citations of 53 undergraduate theses at the College of Arts and Sciences Reading Center in the New Era University.